Respective Roles of Inner and Outer Carbon in Boosting the K+ Storage Performance of Dual‐Carbon‐Confined ZnSe. Issue 5 (19th December 2021) - Ruan, Jiafeng; Zang, Jiahe; Hu, Jiaming; Che, Renchao; Fang, Fang; Wang, Fei; Song, Yun; Sun, Dalin
Abstract: Potassium‐ion batteries (PIBs) have been considered as potential alternatives for lithium‐ion batteries since there is a demand for better anode with superior energy, excellent rate capability, and long cyclability. The high‐capacity zinc selenide (ZnSe) anode, which combines the merits of conversion and alloying reactions, is promising for PIBs but suffers from poor cyclability and low electronic conductivity. To effectively boost electrochemical performance of ZnSe, a "dual‐carbon‐confined" structure is constructed, in which an inner N‐doped microporous carbon (NMC)‐coated ZnSe wrapped by outer‐rGO (ZnSe@i‐NMC@o‐rGO) is synthesized. Combining finite element simulation, dynamic analysis, and density functional theory calculations, the respective roles of inner‐ and outer‐carbon in boosting performance are revealed. The inner‐NMC increased the reactivity of ZnSe with K + and alleviated the volume expansion of ZnSe, while outer‐rGO further stabilized the structure and promoted the reaction kinetics. Benefiting from the synergistic effect of dual‐carbon, ZnSe@i‐NMC@o‐rGO exhibited a high specific capacity 233.4 mAh g −1 after 1500 cycles at 2.0 A g −1 . Coupled with activated carbon, a potassium‐ion hybrid capacitor displayed a high energy density of 176.6 Wh kg −1 at 1800 W kg −1 and a superior capacity retention of 82.51% at 2.0 A g −1 after 11000 cycles. Abstract : An inner N‐doped microporous carbon (NMC) coated ZnSe wrapped by outer‐rGO (ZnSe@i‐NMC@o‐rGO) is synthesized. As expected, the ZnSe@i‐NMC@o‐rGO with "dual‐carbon confinement" structure is used to assemble potassium‐ion hybrid capacitors, exhibiting an extraordinarily energy density of 176.6 Wh kg −1 at 1800 W kg −1 and a superior capacity retention of 82.51% even after 11 000 cycles.